2022
DOI: 10.21203/rs.3.rs-1763604/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of age and prior COVID-19 on BBIBP-CorV (Sinopharm) vaccination- induced antibody responses in a region with high seroprevalence

Abstract: Introduction Sinopharm (BBIBP-CorV) inactivated virus vaccination for COVID-19 has been administered widely in Pakistan. We investigated the dynamics of BBIBP-CorV -induced antibody responses over a 24 week period in a region with a high seroprevalence. Methods Study subjects (n = 312) were followed up over a 24-week period between May and August 2021. Sera were tested for IgG antibodies to spike and the receptor binding domain (RBD). Results Study subjects were 62% female. Twenty-two percent had a prior hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…34 Additionally, a study conducted primarily among the healthcare cohort at AKU found that among individuals vaccinated with BBIBP-CorV, IgG responses to spike protein were enhanced by a history of COVID-19. 35 Our data indicate that HCP who tested negative (controls) had a higher proportion of individuals with a history of RT-PCR-confirmed COVID-19 infection than HCP who tested positive (cases). Furthermore, among HCP with a prior confirmed COVID-19 infection, those who tested negative (controls) had a shorter interval between their previous infection and current testing compared with HCP who tested positive (cases).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…34 Additionally, a study conducted primarily among the healthcare cohort at AKU found that among individuals vaccinated with BBIBP-CorV, IgG responses to spike protein were enhanced by a history of COVID-19. 35 Our data indicate that HCP who tested negative (controls) had a higher proportion of individuals with a history of RT-PCR-confirmed COVID-19 infection than HCP who tested positive (cases). Furthermore, among HCP with a prior confirmed COVID-19 infection, those who tested negative (controls) had a shorter interval between their previous infection and current testing compared with HCP who tested positive (cases).…”
Section: Discussionmentioning
confidence: 62%
“…However, by February 2021, immunoglobulin G (IgG) seropositivity to spike protein was 53% in healthy blood donors in Karachi 34. Additionally, a study conducted primarily among the healthcare cohort at AKU found that among individuals vaccinated with BBIBP-CorV, IgG responses to spike protein were enhanced by a history of COVID-19 35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation